IMPLEMENTASI VOIP MENGGUNAKAN ZRTP, G.729A, DAN FREESWITCH - Budianto, Eko; Rachmawati K, Rr.Yuliana; Andayati, Dina (Jurnal Jarkom, 2015)
ABSTRACTNowadays, the existence of VoIP communication is growing fast. However, communication that is common at this time has not fulfilled the needs of specific users. For particular users, the safety and fluency of the communication is the fundamental needs. This is about VoIP communication that combined between FreeSWITCH as SIP Server, ZRTP as an encryption method to securing communication, and the use of G.729A as an audio codec. To collect the data, it will use the wireshark application for observing Quality of Service during the communication such as delay, jitter, and packet loss. While cain& able application is used for sniffing the process of communication on the network. Using a process of testing using sniffing method, communication on the network which is not using encryption can be caught and read by both wireshark and cain& able application, while communication on the network which is using encryption can not be read by both application. The result of VoIP communication using ZRTP protocol as an encryption method is can not be read and decoded by wireshark and cain& able and the use of codec G.729A is more suiteable for VoIP communication.Â Keywords: VoIP, FreeSWITCH, G.729A, ZRTP, Encryption